EFFICIENCY ANALYSIS OF ESG BANKS BEFORE, DURING, AND AFTER COVID-19 USING DATA ENVELOPMENT ANALYSIS APPROACH - Mario Rosario Wisnu Aji; Elizabeth Fiesta Clara Shinta Budiyono; Yohanes Mario Pratama (Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
The increasing awareness of sustainable practices in the banking sector raises the question of whether such practices have been implemented efficiently in the context of responding to crises before, during, and after the COVID-19 pandemic. This study aims to analyze the efficiency level of banks included in the SRI-KEHATI Index before, during, and after the COVID-19 pandemic. This study employs a quantitative approach using Data Envelopment Analysis (DEA). The data were obtained from the annual reports and sustainability reports of the sampled banks. The findings show that in 2019, BRI had not yet achieved optimal efficiency. In 2020, all banks listed in the SRI-KEHATI Index demonstrated efficient performance. However, inefficiency reappeared in 2021 in BRI and NISP. These findings indicate that the efficiency of ESG-oriented banks changed across the pre-pandemic, pandemic, and post-pandemic periods. The inefficiency observed in 2021 suggests that post-pandemic efficiency recovery was not evenly experienced by all banks. This study indicates the need to strengthen ESG practices alongside efficient resource management. The findings may provide insights for banks and policymakers in promoting more efficient sustainable banking practices.